Effects of resources and costs on diffusion dynamics. (24th February 2010) - Tsai, Yu-Shiuan; Huang, Chung-Yuan
Tipping point is one of the most important assessment indicators of epidemic outbreaks. Due to what we perceive as a too-strong emphasis on ways that the power-law connectivity distribution features of networks affect diffusion dynamics, two important factors have been overlooked: resources and costs. In this paper, we show that at odds with current thinking, a significant tipping point does exist when resources and costs are taken into consideration; and it is possible to control the spread of epidemics in scale-free networks as long as resources are restricted and the costs associated with an infection event are increased.